2016
DOI: 10.1136/archdischild-2016-311822
|View full text |Cite
|
Sign up to set email alerts
|

Haemoglobin discordances in twins: due to differences in timing of cord clamping?

Abstract: Second-born DC and MC twins delivered vaginally have higher Hb levels at birth compared with first-born twins. Intertwin Hb differences in MC twins may partly be related to blood transfusion through the vascular anastomoses. Since DC twins do not have anastomoses, other factors may lead to Hb differences, including differences in timing of umbilical cord clamping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…We were unable to detect any placental transfusion using the PBCC strategy, which is consistent with our previous findings 33. Recent studies in twins (both monochorionic and dichorionic) have shown that when born vaginally, first-born twins have significantly lower haemoglobin levels (at 2 hours and 48 hours after birth) than their second-born twin 34 35. No differences were observed between first-born and second-born twins delivered by caesarean section, providing compelling evidence that placental transfusion may not occur in infants born by caesarean section.…”
Section: Discussionsupporting
confidence: 90%
“…We were unable to detect any placental transfusion using the PBCC strategy, which is consistent with our previous findings 33. Recent studies in twins (both monochorionic and dichorionic) have shown that when born vaginally, first-born twins have significantly lower haemoglobin levels (at 2 hours and 48 hours after birth) than their second-born twin 34 35. No differences were observed between first-born and second-born twins delivered by caesarean section, providing compelling evidence that placental transfusion may not occur in infants born by caesarean section.…”
Section: Discussionsupporting
confidence: 90%
“…In their study, information on the timing of umbilical cord clamping was not available, but they hypothesized that the difference in hemoglobin concentration was because of differences in the timing of cord clamping. In our study, where almost all infants were delivered by CS, the post hoc subgroup analysis of the hematocrit level (in both the ICC and DCC groups) by birth order or chronicity did not yield any statistically significant differences between the groups, which is consistent with the results of Verbeek et al [4] (no significant inter-twin hemoglobin difference in infants born by CS). However, no further conclusion can be drawn due to our limited sample size, and the physiology of placental transfusion in these patients still needs to be elucidated.…”
supporting
confidence: 82%
“…Verbeek et al [4] reported that second-born dichorionic twins vaginally delivered (VD) have higher hemoglobin levels at birth compared with first-born twins. Their results also suggest that twins (monochorionic and dichorionic) delivered by cesarean section (CS) have no significant inter-twin hemoglobin difference.…”
mentioning
confidence: 99%
“…Various studies (8688) showed that the second VD newborn twin had significantly higher hemoglobin concentration at birth and in the first days of life, compared to the first one, both in monochorionic and dichorionic pregnancies.…”
Section: Methodsmentioning
confidence: 99%